The politics of compassion : immigration and asylum policy - Sirriyeh, Ala (Global migration and social change., 2018)
Through case studies from Australia, Europe and the US, this book explores how emotion is central to understanding the formation of immigration policy. The author looks beyond the 'negative' emotions of fear and hostility to examine the politics of compassion in immigration and asylum policy discourse.